2011
DOI: 10.1172/jci44182
|View full text |Cite
|
Sign up to set email alerts
|

A polymorphism in TIM1 is associated with susceptibility to severe hepatitis A virus infection in humans

Abstract: During infection with the hepatitis A virus (HAV), most patients develop mild or asymptomatic disease. However, a small number of patients develop serious, life-threatening hepatitis. We investigated this variability in disease severity by examining 30 Argentinean patients with HAV-induced acute liver failure in a case-control, cross-sectional, observational study. We found that HAV-induced severe liver disease was associated with a 6-amino-acid insertion in TIM1/HAVCR1 (157insMTTTVP), the gene encoding the HA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
79
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(80 citation statements)
references
References 46 publications
0
79
1
Order By: Relevance
“…It might be informative to analyze the enrichment of PS in divergent lentiviruses that are produced from different primate cells, including macrophages and dendritic cells, and investigate their possible relationships to the antiviral activities of TIMs and PS receptors. By extension, the polymorphisms of TIMs in the human population, which have been shown to be associated with asthma and some viral diseases (9,48,49), could hold important links to AIDS pathogenesis and disease progression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It might be informative to analyze the enrichment of PS in divergent lentiviruses that are produced from different primate cells, including macrophages and dendritic cells, and investigate their possible relationships to the antiviral activities of TIMs and PS receptors. By extension, the polymorphisms of TIMs in the human population, which have been shown to be associated with asthma and some viral diseases (9,48,49), could hold important links to AIDS pathogenesis and disease progression.…”
Section: Discussionmentioning
confidence: 99%
“…Human TIM-1 was initially discovered as the receptor for hepatitis A virus (HAV), and has been recently shown to function as a receptor or entry cofactor for Ebola virus (EBOV) and Dengue virus (DV) (5)(6)(7)(8). TIM-1 polymorphisms have been reported to be associated with severe HAV infection in humans (9). More recent studies revealed that TIM-family proteins promote entry of a wide range of viruses, possibly by interacting with virion-associated phosphatidylserine (PS), highlighting a more general role of TIMs in viral infections (10,11).…”
mentioning
confidence: 99%
“…These data underscore the importance of the mucin domain of Tim-1 in regulating immune responses and in the development of atopic diseases. In addition, human NKT cells expressing the long form of TIM-1 showed greater cytolytic activity against HAV-infected liver cells (14). These data on genetic linkage to allergies, HAV infection, and immune responses demonstrate that the length of the mucin domain of TIM-1 has important functional consequences in human immune and infectious diseases, but the actual mechanism by which the TIM-1 mucin domain regulates immune responses has not been analyzed.…”
mentioning
confidence: 95%
“…Interestingly, exposure/infection to hepatitis A virus (HAV) is associated with a reduced risk of developing asthma, atopy, and allergies in humans, and, similarly, Tim-1 has been linked genetically to Th2-driven murine airway hypersensitivity, leading to the identification of the Tapr locus and Tim-1 as an asthma susceptibility gene (6,(10)(11)(12)(13). Although there are small allelic variations in the IgV domain, the genetic linkage to susceptibility to allergy following HAV infection was linked mainly to the length of the mucin domain of TIM-1 (14). An insertion of six amino acids forming a long TIM-1 mucin domain (157insMTTTVP) resulted in protection against asthma and allergy in subjects exposed to HAV (6,(11)(12)(13).…”
mentioning
confidence: 99%
“…Kim et al demonstrate that the expression of the long form of TIM-1 in natural killer T (NKT) cells resulted in greater cytolytic activity against HAV-infected liver cells (6). These data are potentially interesting, yet puzzling.…”
Section: The Role Of Nkt Cellsmentioning
confidence: 99%